The effect of glass flakes reinforcement on the surface hardness and surface roughness of heat-cured poly (methyl methacrylate) denture base material - Haitham T Abdulrazzaq; Mohammed M Ali (College of Dentistry/ University of Baghdad, 2015)
Background: Heat-cured poly (methyl methacrylate) the principal material for the fabrication of denture base have a relatively poor mechanical properties. The aim of this study was to investigate the effect of glass flakes used as reinforcement on the surface hardness and surface roughness of the heat-processed acrylic resin material. Material and method: Glass flakes (product code: GF002) pretreated with silane coupling agent were added to Triplex® denture base powder using different concentrations. A total of 100 specimens of similar dimensions (65 x 10 x 2.5) mm were prepared, subdivided into 2 main groups of 50 specimens for each of the study tests. Ten specimens for the control group and 40 specimens for each of the experimental groups (2%, 3%, 5%, and 7%) glass flakes content. The surface hardness was evaluated using the Shore D hardness test, while the surface roughness was evaluated using a profilometer device that detect the geometry of the specimen unpolished surface. Results were analyzed using the Wilcoxon rank sum test and the 1-way analysis of variance, (P-value 0.05). Results: The surface hardness tended to increase significantly p˂ 0.05 with the increasing flakes concentration, as an increase of 5.12% was recorded in surface hardness for the highest loading level; while the roughness showed a significant increase that remained within the tolerable range -less than 2µm- (significant bacterial colonization would occur if the surface roughness is more than 2µm). Conclusion: The addition of glass flakes to heat-cured poly(methyl methacrylate) enhanced the hardness of the material, the improvement was statistically significant for the higher glass flakes concentrations (5% and7%), while for the surface roughness there were a constant increase in roughness along with the increasing glass flakes content